Theory and Practice of Short Term Economic Forecasting - Misiūnas, Algimantas; Klokova, Vitalija (Ekonomika, 2001)
This paper introduces to short-term forecasting model at macroeconomic level. Model is oriented for evaluation of transitional period tendencies. That’s why it is very useful for Lithuania. Big attention is given to formation of private sector by privatisation of the state property. It is estimated by changes of employment and production in private and public sector. Information used for forecasting covers 6 years (24 quarters). There was transformation of state property to private at that period. Calculations with LAM model carry out for all Baltic and CEFTA countries twice a year. Macroeconomic and Financial Data Centre (M&FDC) of Gdansk University does this. Short-term forecasts are necessary for people responsible for formation of State budget or for estimation of State budget fulfilment. Such forecasts are needful for formation of development programs for other sectors. Authors are improving model by introducing more main indicators of national economy. In future they are going to emphasise the influence of investment process to economic growth. Data of other countries is presented in this paper. Readers become acquainted with macroeconomic tendencies of these countries and they can evaluate tendencies of Lithuanian development critically.